On a sum form functional equation emerging from statistics and its applications - Dhiraj Kumar Singh, Shveta Grover (Results in Nonlinear Analysis, 2021)
In this paper, we obtain the general solutions of a sum form functional equation arising from the expected value of a discrete random variable. The significance of its general solutions in reference to entropies emerging from information theory and diversity index has been discussed.